SPOT WELDING COPPER - 1% Cr ELECTRODE TIPS PRODUCED VIA EQUAL CHAN NEL ANGULAR PRESSING - L.B. Hussain; Ali A. Aljuboury; M.A.M. Gebril; Nurulakmal Moh Sharif (Universitas Gadjah Mada, 2005)
A sharp 120o Equal channel angular pressing (ECAP) was applied at room temperature to refine the grains sizes of pure copper and copper - 1% Chromium alloy for spot welding electrode tips application. Initially deformation behavior was investigated with the position using colorful plasticine as work piece followed by copper alloy. It was found the deformation at the central part of the work piece is heavily sheared than the outer part. Optical and Scanning electron microscopy were used to study the progress of grain refining under the influence of rotation and number of passes during pressing. The influence of elongated fibrous nano graines on electrical conductivity and hardness were discussed. Shear test of spot welded 303 stainless steel indicated that nano structural Cu-1% Cr electrode tips used showed superior results compared to commercial electrodes.